Marching and Memory in Early Twentieth-Century Quebec: La Fête-Dieu, la Saint-Jean-Baptiste, and le Monument Laval - Rudin, Ronald (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1999)
AbstractDuring a three-day period in June 1908, 250,000 people attended a series of elaborate celebrations in Quebec City in honour of Mgr François de Laval, the first bishop of Quebec, upon the bicentenary of his death. A monument to Laval was unveiled on the middle day, in between the two most important summer festivals of the French-Canadian calendar. The Fête-Dieu (Corpus Christi) celebrations preceded the unveiling, while the Fête de la Saint-Jean-Baptiste followed. In planning the festivities, particular care was devoted to organising processions through the streets of Quebec City. These two processions, the former organised by clerics and the latter by laymen, sent somewhat contradictory messages to both spectators and participants. Nevertheless, they formed part of a collective effort by clerical and lay leaders to claim the streets of Quebec, in the process asserting their power at a time when French-Catholic society was being challenged from various quarters.